2019
DOI: 10.1080/14786419.2019.1582044
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic content and bioactivities of Crataegus oxyacantha L. (Rosaceae)

Abstract: Solid-Liquid Extraction (SLE) using solvent of different polarities (CHCl 3 , EtOAc, and n-BuOH) has been applied to leaves and fruits from (Crataegus oxyacantha L.), a deciduous shrub with an expected rich phytochemical profile. The total polyphenols content and the radical scavenging activity of each extract were evaluated. These extracts were analyzed by HPLC-DAD and rutin, quercetin-3-glucoside, caftaric and caffeic acid had been positively identified. The phytochemical study of the ethyl acetate extract o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…Their employment as additives is broadly distributed in industry field to delay, prevent or eliminate damage caused by oxidation. Recently, some plant extracts have been reported to have good antioxidant and antimicrobial properties due to their polyphenolic and protein compounds (Piscopo et al 2019;Tortora et al 2019;Benabderrahmane et al 2018;Benabderrahmane et al 2019). Due to its complex composition, containing antioxidant dietary fibre, as well as extractable and non-extractable polyphenol content, grape marc extracts have a great potential to display extensive uses in agricultural, pharmaceutical and cosmetic industries among others (Bargiacchi et al 2017;Placha et al 2013;de O Ribeiro et al 2018;Tayengwa and Mapiye 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Their employment as additives is broadly distributed in industry field to delay, prevent or eliminate damage caused by oxidation. Recently, some plant extracts have been reported to have good antioxidant and antimicrobial properties due to their polyphenolic and protein compounds (Piscopo et al 2019;Tortora et al 2019;Benabderrahmane et al 2018;Benabderrahmane et al 2019). Due to its complex composition, containing antioxidant dietary fibre, as well as extractable and non-extractable polyphenol content, grape marc extracts have a great potential to display extensive uses in agricultural, pharmaceutical and cosmetic industries among others (Bargiacchi et al 2017;Placha et al 2013;de O Ribeiro et al 2018;Tayengwa and Mapiye 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Hawthorn is a semi-evergreen shrub or small tree, that usually has thorns, mostly growing up to 5–15 m [ 12 , 13 ]. Leaf morphology, seed traits, the number of seeds and the color of the fruits are highly diverse.…”
Section: Botanical Aspectsmentioning
confidence: 99%
“…Good yields of polyphenols extracted from hawthorn could be obtained [ 13 ]. Specifically, various chromatographic profiles revealed that both the leaves and berries of C. monogyna are rich in isoquercitrin, vitexin, quercetin, rutin and vitexin-2- rhamnoside.…”
Section: Phytochemical Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The work of Nabavi et al focused on the polyphenolic composition of C. monogyna Polyphenol compounds from C. oxyacantha extracts, including epicatechin, epicatechin gallate (ECG), rutin, caffeic, and caftaric acids, were identified using HPLC-DAD and LC-MS/MS techniques [27]. In a study, UV/MS analysis coupled with 1D/2D nuclear magnetic resonance (NMR) spectroscopy was used to detect the compounds extracted from the ethyl acetate extract of C. oxyacantha, which included naringenin, epicatechin, quercetin-3-O-β-glucoside, and quercetin [28]. The presence of rutin and quercetin obtained from C. oxyacantha extracts using HPLC was also reported [29].…”
Section: Phytochemical Composition Of Hawthornmentioning
confidence: 99%